Impact of and coping with post-traumatic symptoms of refugees in temporary accommodations in Germany: a qualitative analysis - Rzepka-Marot, Irja; Zehetmair, Catharina; Roether, Emma; Kindermann, David; Cranz, Anna; Junne, Florian; Friederich, Hans-Christoph; Nikendei, Christoph (International journal of environmental research and public health, 2022)
Due to pre-, peri- and post-migratory stress factors, refugees often experience higher levels of psychological stress than the general population. Post-traumatic stress disorder, in particular, has an increased prevalence in the refugee population. However, living conditions in the early post-migratory phase are characterized by many challenges. In the present qualitative study, 14 refugees with symptoms of PTSD from temporary accommodations in Germany were interviewed in semi-structured interviews about their individual experiences of the impact of their trauma sequelae symptoms on their current living conditions and interactions. Participants reported dealing with post-traumatic symptoms primarily through distraction strategies, such as working or learning the language or social interaction. Many reported a sense of mistrust as a result of traumatic experiences. Current stress factors cited included uncertain asylum status, worry about family members and lack of ability to influence living situations. The interactions between the post-traumatic symptoms and the living conditions of the refugees were highlighted. The effects of the symptomatology of trauma sequelae and the framework conditions under which refugees live can lead to aggravated psychological distress. Therefore, special attention must be paid to refugee mental health care.